Larval Physiological Responses to Temperature Across the European Distribution Range of a Global Invader at Home: The Shore Crab Carcinus maenas - Jan Phillipp Geißel; Noé Espinosa‐Novo; Luis Giménez; Nicole Aberle; Gro I. van derMeeren; Steffen Harzsch; Maarten Boersma; Gabriela Torres (Ecology and Evolution, 2025)
ABSTRACT In marine species with complex life cycles, thermal tolerance is usually narrower in larvae than in adults. Hence, range contraction and expansion, as a consequence of climate change, may be enhanced or hampered by among‐population variability in the thermal tolerance of larval stages. We quantified the performance (i.e., survival, development, and growth) of larvae of the shore crab Carcinus maenas at different temperatures (range 9°C to 27°C in steps of 3°C) in populations located towards the limits of the European distribution range (South: Vigo, Spain; North: Bergen and Trondheim, Norway). We hypothesised that, given the geographical distance, larvae from northern populations would show increased tolerance to low temperatures while those from southern populations would show increased tolerance to high temperatures. Such patterns would enhance poleward range expansion and counteract contraction as compared with a scenario where thermal tolerance does not change along the latitudinal gradient. Populations from southern Europe (Spain) showed slightly increased survival at higher temperatures compared to those further north and in invasive North American populations. However, there was little variation in larval tolerance between populations of Northern Spain and Norway: survival and growth rates were low at temperatures 9°C and 27°C. Larvae from the northernmost European populations (Norway) showed significantly shorter duration of development at low temperatures, which might have an adaptive value, contingent on the actual pattern of temperatures experienced during the larval phase. Further range expansions (or contractions) are likely to be driven solely by increasing temperatures unless populations located right at the range limit show increased tolerance to low (or high) temperatures.